Vadba na napotnico kot oblika vključevanja kineziologa v delovanje zdravstvenega doma - Spudić, Darjan (Šport (Ljubljana), 2018)
A lack of physical activities or the, so called, sedentary life style is a vital cause of many chronical diseases of the modern times. Therefore, the idea of systematically including physical activity into health care is not unfamiliar. Some European countries have already established exercise via medical referrals and it has proven to bring positive effects on health and lowered the costs of medical care. Slovenia is, unfortunately, still in the process of implementing the aforementioned process. The purpose of this article is to present in what way is a kinesiologist implemented into the daily operations of the Healthcare Centre of Črnomelj. In short, the medical personnel of the healthcare centre established an organised form of cooperation with the kinesiologists by referring people with specific needs to them, which allowed for a systematic and wholesome treatment of patients. The kinesiological treatment via a medical referral has, until now, brought positive results, confirming it is a wholesome and economic method of health care. The systematisation of work additionally increased the functional value and contribution of the kinesiologist on all levels of preventive medical activity and, therefore, reinforces the fact that they should continue to be included in the world of health care.
Keywords: kineziologi; kineziologija; napotnice; obravnava; preventiva; vadba